Aplikasi edible coating pati bekatul terhadap mutu buah tomat (Lycopersicum esculentum Mill.) - Nadhifah, Ashma; Sholahuddin, Sholahuddin; Saputri, Nur Endah (Universitas Muhammadiyah Mataram, 2025)
Tomatoes are classified as climacteric fruit that are susceptible to damaged after harvest. The use of edible coatings is expected to be a damage reduce alternative by forming a thin layer on the surface of the product that acts as a barrier to water loss and gas exchange to slow the damage process. This research aims to determine the best concentration of rice bran starch and storage duration that can maintain the quality of tomatoes as room temperature. The research design used was a factorial Randomized Group Design with concentrations of rice bran starch were 0% (control), 1%, 2%, 3%, 4%, and 5%, and storage durations of day-0, 4, 6, and 10. The results showed that a concentration of 5% rice bran starch was the most effective in maintain weight weight loss (5.00%), total soluble solids (5.16 ̊ brix), total acids (0.32%), vitamin C content (29.33 mg/100g, and red color (15.35) in tomatoes for 10 days at room temperature.